Thermal characterization of anaerobic sludges from wastewater treatments applied to biological generation of H2 - Torquato, Lilian Danielle de Moura [UNESP]; de Almeida, Sônia [UNESP]; de Oliveira, José Eduardo [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Springer Nature, 2017)
A wide variety of organic residues may be used as energy source such as anaerobic sludge from wastewater treatment systems. However, due to inherent differences in composition, the proper characterization of these biomasses is essential to support their reuse through any conversion process. The aim of this study was the employment of thermal analysis techniques (TG/DTG and DTA) to perform the characterization of anaerobic sludges from different wastewater treatment plants (industrial and municipal), which were further applied for biological production of H2. The different profiles observed through thermal characterization support the application of these residues as inocula, confirming their potential for H2 production, while demonstrating the main causes for the different yields obtained (mol H2 mol−1 sucrose): 0.9 from sludge of brewery industry and 2.0 from sludge of municipal wastewater treatment plant, corresponding to the overall yields of 10.8 and 25%, respectively. These results confirm the versatility of thermal analysis techniques for biomass characterization, focused on its application for power generation. It is urgent to adopt more sustainable and cost-effective solutions for their management, considering a large amount of residues daily generated in both treatment processes addressed; therefore, biohydrogen production by anaerobic digestion may be a promising alternative for the reuse of both residues as it promotes their transformation from costly and potentially polluting waste into clean and renewable energy sources. The development of this anaerobic process is even more attractive in countries as Brazil, where the weather conditions are naturally favorable.
Keywords: Anaerobic sludge; Biohydrogen generation; Biomass; Brewery industry; Thermal analysis